2021
DOI: 10.2147/clep.s298770
|View full text |Cite
|
Sign up to set email alerts
|

Positive Predictive Value of Diagnostic Codes for Inflammatory Bowel Disease in the Danish National Patient Registry Among Individuals 50+ Years, Using Patient Records as Reference Standard

Abstract: Purpose: Inflammatory bowel diseases (IBD), including Crohn's disease (CD) and ulcerative colitis (UC), are chronic diseases. The aim was to validate diagnoses of IBD among patients aged 50+ years in the Danish National Patient Registry (NPR) by comparison with patient medical records. Patients and Methods: Men and women in the Diet, Cancer and Health (DCH) cohort were linked to NPR, and cases with a diagnosis of IBD and their respective hospital records were identified. Validation was performed by comparing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Our findings in the studied pediatric population are almost identical to earlier Swedish and Danish studies, assessing PPVs of the same register-based IBD definition in mostly or exclusively adult populations. 11 , 32 Two previous studies from Sweden and Denmark found markedly higher PPVs for IBD subtypes in adult patients (PPV = 89–97%), but these studies only included patients with confirmed IBD. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings in the studied pediatric population are almost identical to earlier Swedish and Danish studies, assessing PPVs of the same register-based IBD definition in mostly or exclusively adult populations. 11 , 32 Two previous studies from Sweden and Denmark found markedly higher PPVs for IBD subtypes in adult patients (PPV = 89–97%), but these studies only included patients with confirmed IBD. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…The need for much more complex algorithms to identify IBD in Canada and Israel 35 , 36 compared to the corresponding Danish and Swedish algorithms 11 , 32 , 34 is likely due to several differences between the healthcare systems and databases used. The Canadian algorithms were created based on billing claims in systems where diagnostic codes for IBD seem to have been used also before a definitive diagnosis had been confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of IBD diagnosis codes in the DNPR has reported a high completeness (94%) and a positive predictive value (PPV) of 90% and 98% for UC and CD, respectively, 51 yet lower in IBD patients aged above 50 52 . Potential misclassification would likely be non‐differential with bias towards the null.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have used different diagnostic criteria, and no single ‘gold standard’ exists. 22 23 34–36 The length of the hospital admission was used to decrease the risk of misclassification (false positives) of patients with only one diagnosis. Among those patients with only one diagnosis registered but with a hospital admission lasting at least 7 days, 618 (13.8%) were diagnosed in the last year of the inclusion period (2018).…”
Section: Discussionmentioning
confidence: 99%